Effect of Aggregate Gradation and Filler Content on the Rutting Resistance of Modified Colored Hot Mix Asphalt - Naji, Samer Ali; Abed, Alaa H. (Al-Nahrain Journal for Engineering Sciences, 2021)
Rutting is considered as the most generated distress in Iraqi roads as a result of the high temperature and excessive traffic load. So, it is essential to utilize polymer modified binder to increase the performance of pavements. The objective of this paper is to assess the effect of aggregate gradation and filler content on the rutting formation of Colored Hot Mix Asphalt CHMA. The HMA was colored by using iron oxide as filler to produce red HMA. Two blends were used: fine and coarse with two different types of filler iron oxide for CHMA and limestone for conventional HMA with two filler content 6% and 10%. Neat (AC 40-50) and modified asphalt (AC 40-50 + 4%SBS) were used. Tests are held on adding 4% Styrene Butadiene Styrene )SBS( by the weight of neat asphalt (AC 40-50) to raise the performance grade by two grades from PG (64-16) to PG (76-16) [1] and [2]. The wheel tracking test is used to assess the rut depth of the CHMA. The test results showed that the using iron oxide with neat asphalt increase the rut depth resistance by 200 and 400 failure load cycles than mixtures using limestone (cycles that mix reach 25 mm rut depth) for fine and coarse mix respectively. Also, the effect of gradation shows that the fine mixture fails at 4000 cycles while the coarse mixture fails at 1800 cycles for 6% limestone mixtures. Increasing the iron oxide content from 6% to 10% leads to increase the failure load cycles by 2200 and 1200 cycles for fine and coarse mixture respectively using modified asphalt. The fine mixture with 10% iron oxide using modified asphalt gives the best performance with 7000 cycles than the coarse mixture with 10% filler content and modified asphalt with 4000 cycles. irrespective the filler and type of binder, the dense mixtures using iron oxide as filler exhibit better resistance to rutting formation than coarse mixtures.